Perbandingan nilai fisiologis kardiorespirasi dan suhu rektal anjing kampung dewasa dan anak - Agik Suprayogi; Huda S. Darusman; Iqbal Ngabdusani (Jurnal Ilmu Pertanian Indonesia, 2009)
Dog is man's favorite companion animal and they are also beneficial as an animal model in biomedical research. So far, the Indonesian native dog's physiological values for diagnostic or research purposes, was based on literature which differed in breeds, geography and age variety. Furthermore, there is little publication on Indonesian native's dog physiological value which emphasize on its age variety, specially its comparative study between adult and puppies. Comparative parameters which were used in this study were heart rate {HR), respiratory rate {RR), non-invasive blood pressure {NIBP) and rectal temperature {RT). The study utilized fifteen Indonesian native dogs. The result showed a significant {p< 0.05) higher HR's values on puppies to adult, which are 152.50±14.76 and 95.93±23.7 beat per minute), respectively, while the RT's were lower on puppies to adults {37.53±0.29 and 38.23±0.73 °C, respectively). The NIBP's values were significantly lower on puppies to adult, which are systole {83.93±13.29 Vs 129.68±24.45 mmHg), diastole {37.50±16.31 Vs 72.96±20.33 mmHg) and mean blood pressure values {58.21±13.30 Vs 91.82±24.34 mmHg). The insignificant result was found on RR values which are 26.50±7.93 and 28.21±14.34 for puppies and adult, respectively. The main reason for the differences in above parameters among puppies and adult can be defined by their metabolic rate and growth process.